Identification Model Of Job Description, Compensation, Rotation Work And The Impact On Employee Performance - Anwar, Yohni; Dewanto, Vishnu (Publisher Cv. Inara, 2022)
The research objective is to improve the competence and performance of employees at Indosat Ooredo outlets based on the SEM model on the variables of training and development, job description , compensation and job rotation. The method of analysis in this study uses a Structural approach Equation Modeling (SEM). The SEM model is used to predict the training and development model, job description , compensation and job rotation on work culture and employee performance. The population in this study were 120 employees at Indosat Ooredoo outlets . The sample of this research data was taken based on the census sample, that is, all of the population was used as a sample, namely 120 respondents. The data used is primary data where respondents get data for the questionnaire. Meanwhile, the data collection method used in this study was a questionnaire and interviews. The results showed that direct competence had no effect on job satisfaction while job description, compensation and job rotation had a significant effect on job satisfaction. Directly competence, job description and job rotation and job satisfaction have a significant effect on employee performance while compensation is not significant on employee performance. Indirectly, satisfaction has a significant role in mediating competence, job description and compensation on employee performance, while job satisfaction has no role in mediating job rotation on employee performance.